A NEW PARADIGM OF CHARACTER EDUCATION: HOW THE ROLE OF SCHOOLS IN INCREASING ENVIRONMENTAL AWARENESS - Zahrah, Fatimatuz; Rahmat, Rahmat (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
School as a place for someone to receive knowledge, skills, and attitudes must be able to instill character in students. One of the important characteristics to be instilled and fostered in students is the character of caring for the environment. This shows that schools have a role to increase students' environmental awareness. This study examines the role of schools in increasing students' environmental awareness by using a new paradigm of character education. The literature review was conducted on 25 articles from 2017 to 2022 and focused on research progress on the role of schools in increasing environmental awareness. A critical review was carried out to re-examine the character education and environmental awareness, the role of schools in increasing environmental awareness, and the positive impact of strengthening the character of caring for the environment. The results of the analysis show that character education of faith in God, independence, and cooperation can increase environmental awareness. The school's role in increasing environmental awareness is by internalizing the value of caring for the environment in the curriculum, extracurricular activities, school culture, and exemplary. The positive impact of strengthening the character of caring for the environment is the progress of learning motivation, creativity and productivity, and the improved character of students. The conclusion of this study is to provide an appropriate reference for future researchers by identifying the role of the community and government in strengthening the environmental awareness of the Indonesian people